1966
DOI: 10.1177/004051756603601201
|View full text |Cite
|
Sign up to set email alerts
|

Treatments of Wool in Organic Solvents and Their Effect on the Urea-Bisulfite Test

Abstract: Treatment of wool in a number of organic solvents reduces both its cystine content and its solubility in urea-bisulfite. Some reagents attack the disulfide bond in such a way that hydrogen sulfide is evolved. As, however, no lanthionine has been found, and the effect due to lysinoalanine is not yet known, it could be claimed that no correlation exists between cystine breakdown and reduction in solubility. The latter is probably due to physical changes of the keratin molecule, and it is affected by the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

1968
1968
1978
1978

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
1
0
3
Order By: Relevance
“…Lennox [7] observed that after mild treatment in hot water there was a small but significant decrease in the extractability of wool by alkaline thioglycollate (see also ref. [ 13 ] ) . This work has now been extended and the results in Table II show that heating in water also renders the wool less soluble in alcoholic sodium iodide-tributyl phosphine.…”
Section: Definition Of Solubility Test Conditionsmentioning
confidence: 99%
“…Lennox [7] observed that after mild treatment in hot water there was a small but significant decrease in the extractability of wool by alkaline thioglycollate (see also ref. [ 13 ] ) . This work has now been extended and the results in Table II show that heating in water also renders the wool less soluble in alcoholic sodium iodide-tributyl phosphine.…”
Section: Definition Of Solubility Test Conditionsmentioning
confidence: 99%
“…Άπό τίνος όμως χρόνου εφαρμόζεται ειδική δοκιμασία δια τήν μέτρησιν της διαλυτότητος του έρίου εις διάλυμα ούρίας-όξίνου θειώδους νατρίου και ακόμη έχει εύρεθή οτι ή διαλυτότης αυτή επηρεάζεται ύπό αντιδραστηρίων ομοίων προς έκεϊνα τα όποια προ καλούν τήν μετουσίωσιν των διαλυτών πρωτεϊνών, ως π.χ. κατεργασία τοΰ έρίου δι 5 οξέων 74 , αλκαλίων 74 , ζέοντος ύδατος 74 , αλκοόλης 75 κλπ.…”
Section: μετουσιωσις των πρωτεϊνωνunclassified
“…Ή μέθοδος αύ'τη έχρησιμοποιήθη επίσης δια τήν πιστοποίησιν τών με ταβολών, αϊ όποΐαι επιτελούνται είς τό εριον κατά τάς διαφόρους κατεργα σίας, ώς π.χ. ή εκθεσις είς ύψηλήν θερμοκρασίαν 101 ή κατεργασία με οργα νικούς διαλύτας 75 , κλπ.…”
Section: διαλυτότης είς διάλυμα ούριας -όξινου θειώδους νατρίουunclassified
See 1 more Smart Citation